Social Constructionism : Sources and Stirrings in Theory and Practice / [electronic resource] - Lock, Andy; Strong, Tom (Cambridge : Cambridge University Press, 2010)
Social Constructionism: Sources and Stirrings in Theory and Practice offers an introduction to the different theorists and schools of thought that have contributed to the development of contemporary social constructionist ideas, charting a course through the ideas that underpin the discipline. From the New Science of Vico in the 18th century, through to Marxist writers, ethnomethodologists and Wittgenstein, ideas as to how socio-cultural processes provide the resources that make us human are traced to the present day. Despite constructionists often being criticised as 'relativists', 'activists' and 'anti-establishment' and for making no concrete contributions, their ideas are now being adopted by practically-oriented disciplines such as management consultancy, advertising, therapy, education and nursing. Andy Lock and Tom Strong aim to provoke a wider grasp of an alternative history and tradition that has developed alongside the one emphasised in traditional histories of the social sciences.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Social constructionism; Sociology